(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
The goal of the research was to determine the properties of the microbial barrier TENCEL00ae knitted fabrics intended for medical bras. The samples were tested according to a new method developed in the earlier research by the same authors. The most resistant forms of microorganisms of a pathogenic bacterial endospore of the Bacilllus genus were used to investigate microbial barrier permeability. Based on the samples tested and their characteristics, medical bra construction was developed with the aim of reducing irritation for the body part that underwent surgery. The data on the forms and measures were obtained using a 3D body scanner.